Optimizing mass rabies vaccination program in Bali dog population - Darmawan, R.D.; Jatikusumah, A.; Sunandar; Widyastuti, M.D.W.; Arief, R.A.; Basri, C.; Putra, A.A.G.; Willyanto, I.; Estoepangestie, S.; Mardiana, I.; Gilbert, Jeffrey; Hampson, Karen J. (Khon Kaen University, 2013)
Since 2008, 145 human rabies deaths have occurred during an ongoing epidemic in Bali with last victims reported in April 2012, while rabies cases in dogs remained still often reported, with increase cases in puppies (age< 6 months, 39%). The incidence of human deaths due to rabies has dropped drastically (up to 90 %) since the inception of mass dog vaccination in October 2010. A high vaccination coverage is the key success in mass vaccination; yet, arguably, the dynamics and structure of dogs population in Bali become another challenging issue. We present here results of a household survey on owned dogs (n=17,376) and transect for free roaming dogs (n=1972 observation) in 37 randomly selected villages of Bali. This survey was part of the ILRI/EcoZD project on Optimizing Rabies Control Program in Bali - An Ecohealth Approach. According to the survey, there is a significant difference in vaccination coverage between adult dogs (with age range above 1 year old) and puppies (less than 1 year old). The differences were about 91.42 % and 43.95 %. This is due to the rapid growth of population of puppies. In our study growth population rates of puppies per year, ranged from 1.7 -3.5 times (each birth ranged from 3.84-4.46 (95% CI) with an average number of puppies of 4,15 puppies per birth) and vaccination targets that focuses just on adult dogs. Therefore to optimize mass rabies vaccination targeting eliminating rabies in Bali, concerted effort should be made to vaccinate puppies, free-roaming dogs particularly in rural areas. In addition to that, the population of dogs has to be controlled so that the vaccination coverage can be improved.